Option Pricing on the GPU with Backward Stochastic Differential Equation - Ying Peng; Bin Gong; Hui Liu; Bin Dai (2011 Fourth International Symposium on Parallel Architectures, Algorithms and Programming, 2011)
In this paper, we develop acceleration strategies for option pricing with non-linear Backward Stochastic Differential Equation (BSDE), which appears as a robust and valuable tool in financial markets. An efficient binomial lattice based method is adopted to solve the BSDE numerically. In order to reduce the global memory access frequency, the kernel invocation is avoided to be performed on each time step. Furthermore, for evaluating the affect of load balance to the performance, we provide two different acceleration strategies and compare them with running time experiments. The acceleration algorithms exhibit tremendous speedup over the sequential CPU implementation and therefore suitable for real-time application.